The Impact of Scientific and Technical Training on Improving Routine Collection of Antenatal Care Data for Maternal and Foetal Risk Assessment: A Case Study in the Province of South Kalimantan, Indonesia - Dewi Anggraini; Mali Abdollahian; Kaye Marion; Supri Nuryani; Fadly Ramadhan; Rezky Putri Rahayu; Irfan Rizki Rachman; Widya Wurianto (Journal of Pregnancy)
Objectives. First, to assess the impact of scientific and technical training on midwives’ abilities in collecting and recording the results of routine antenatal care examinations. Second, to explore midwives’ views with regard to factors affecting their abilities to successfully complete the data documentation tasks. Methods. The study was conducted in South Kalimantan, Indonesia (April 2016-October 2017). Nineteen urban and rural midwives were selected. Access to antenatal care information on 4,946 women (retrospective cohort study) and 381 women (prospective cohort study) was granted. A descriptive and exploratory design was used to describe midwives’ abilities and challenges pertaining to timely collection and recording of results concerning antenatal care examinations. Results. Scientific and technical training has significantly improved the average amount of recorded antenatal care data (from 17.5% to 62.1%, p-value < 0.0005). Lack of awareness, high workload, and insufficient skills and facilities are the main reasons for the database gaps. Conclusions. The training has equipped midwives with scientific knowledge and technical abilities to allow routine collection of antenatal care data. Provision and adequate use of this information during different stages of pregnancy is crucial as an evidence-based guideline to assess maternal and foetal risk factors to ending preventable mortality.